EXPERIMENTAL MODEL OF NON-GUNSHOT FRACTURES OF THE LOWER JAW - Бєліков, Олександр; Рощук, Олександра; Бєлікова, Наталія; Сорохан, Микола; Алієв, Вугар (SWorldJournal, 2025)
The article summarizes the results of clinical and experimental studies of the formation of mandibular fractures of non-gunshot origin depending on the direction and angle of impact, the features of destruction of its surface during jaw opening and closin